High burden of recurrent cardiovascular events in heterozygous familial hypercholesterolemia: The French Familial Hypercholesterolemia Registry. (October 2018) - Béliard, Sophie; Boccara, Franck; Cariou, Bertrand; Carrié, Alain; Collet, Xavier; Farnier, Michel; Ferrières, Jean; Krempf, Michael; Peretti, Noël; Rabès, Jean-Pierre; Varret, Mathilde; Vimont, Alexandre; et al.
Abstract: Background and aims: Cardiovascular risk is high in heterozygous familial hypercholesterolemia (HeFH). The objective of this study was to describe recurrent cardiovascular events in selected patients with HeFH attending lipid clinics in France. Methods: We included 781 patients with a clinical (Dutch Lipid Clinic Network score ≥ 6) or genetic diagnosis of HeFH who had experienced a first cardiovascular event (myocardial infarction, percutaneous coronary intervention or coronary bypass, unstable angina, stroke, peripheral arterial revascularization or cardiovascular death) and were enrolled in the French Familial Hypercholesterolemia Registry (November 2015 to March 2018). Results: The first cardiovascular event occurred at the mean age of 47 years (interquartile range 39–55) in a predominantly male population (72%); 48% of patients were on statin therapy. Overall, 37% of patients had at least one recurrent cardiovascular event (mean of 1.8 events per patient), of which 32% occurred in the 12 months after the index event; 55% of events occurred >3 years after the first event. Mean LDL-C at the last clinic visit was 144 ± 75 mg/dL (132 ± 69 mg/dL for patients on high-potency statin therapy and 223 ± 85 mg/dL for untreated patients). Conclusions: The rate of recurrent cardiovascular events was high in French patients with HeFH in secondary prevention. The detection of FH during childhood is crucial to prevent CV events at a young age by early initiating statin therapy. There is a clear urgent need to expand the actual very small target population which can be treated with the PCSK9 inhibitor in France. Highlights: One in two HeFH patients is not treated with statins at the time of the first CV even. 37% of HeFH patients have CV recurrences after a first CV event. Nearly half of the CV recurrences occurred more than 3 years after the first event.